Profitabilitas pada perbankan syariah di Indonesia: Studi pengaruh faktor internal dan eksternal - Indri Yaumil Fadila; Dadang Hermawan (Journal of Islamic Economics and Business, 2021)
The purpose of this study is to find out and analyze internal factors and external factors of Islamic banking that can affect the profitability of Islamic Banking both simultaneously and partially. The dependent variable used in this study is incomesmoothing which is proxied by Profitability which is proxied by the Return On Assets (ROA), while the independent variables in this study are Capital Adequacy proxied by the Capital Adequacy Ratio (CAR), Finance Risk proxied by Non Performing Finance (NPF), Inflation, and BI Rate. This research was conducted at Sharia Commercial Banks in Indonesia for the period 2015. The population in this study is Islamic banking in Indonesia and the sample used is Sharia Commercial Banks in Indonesia, which until 2019 amounted to 14 banks. The type of data used is secondary data that is data from the been published by Otoritas Jasa Keuangan. The type of data used is secondary data obtained from twww.ojk.com and www.bi.go.id. The analysis technique used in this study is Multiple Regression analysis using the SPSS 22 program tool.Kata kunci: Capital Adequacy Ratio, Non Perfoming Finance, Return On Asset, Inflation BI rate